Studi Farmakovigilans Pengobatan MDR-TB pada Pasien Rawat Jalan di RSUD Embung Fatimah Kota Batam Tahun 2020: Study of MDR-TB Treatment Pharmacovigilans in Outpatients at Embung Fatimah Hospital Batam City in 2020 - Sri Ana Setianingsih; Delladari Mayefis; Helmi Arifin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Pharmacovigilance is a science related to collecting, detecting, monitoring, assessing, and preventing side effects of pharmaceutical products. The design of this research is retrospectively descriptive. To understand the characteristics of MDR-TB patients and the side effects of the drug that MDR-TB patients feel. The research was conducted between January 2020 – June 2020. The research was conducted at Embung Fatimah Hospital. The number of confirmed patients with MDR TB was 24 patients, 9 male (37.5%) and 15 women (62.5%); the average MDR-TB patient aged 26-45 years (54.20%), Batu Aji (45.83%) be the place most exposed to MDR-TB with a social history of smoking, drugs, and alcohol. The results showed patients who experienced 41.7% anorexia side effects, 100% nausea, 100% vomiting, reduced appetite by 37.5%, 79.2% pain at the injection site, 79.2% joint pain, 58.3% reduced hearing and 25% vertigo. In conclusion, most side effects are nausea and vomiting.